Tithe : a modern faerie tale - Black, Holly (New York : Simon Pulse, 2004)
Sixteen-year-old Kaye, who has been visited by faeries since childhood, discovers that she herself is a magical faerie creature with a special destiny.
750
Accelerated Reader AR
A YALSA 2003 book.
Keywords: Fairies -- Fiction; Magic -- Fiction